Antibody and TLR7 Agonist Delay Viral Rebound in SHIV-Infected Monkeys - Borducchi, Erica N. (Nature, 2018)
The latent viral reservoir is the critical barrier for the development of an HIV-1 cure. Previous studies have shown that potent HIV-1 Env-specific broadly neutralizing antibodies (bNAbs) administered at the time of antiretroviral therapy (ART) discontinuation can exert direct antiviral effects, but whether bNAbs can target the viral reservoir during ART suppression remains unknown. Here we show that the V3 glycan-dependent bNAb PGT121 together with the TLR7 agonist vesatolimod (GS-9620) administered during ART suppression delayed viral rebound following ART discontinuation in SHIV-SF162P3-infected rhesus monkeys that initiated ART during early acute infection. Moreover, the subset of PGT121+GS-9620 treated monkeys that did not show viral rebound following ART discontinuation also did not reveal virus by highly sensitive adoptive transfer and CD8 depletion studies. These data demonstrate the potential of bNAb administration together with innate immune stimulation as a possible strategy to target the viral reservoir.